Puppetry-Based Literacy as a Means of Early Childhood Character Education - Abror, Moh. Rayhan Danil; Sadewo, Satriyo Panji; Yasmin, Saila Irfany; Citra Sarasmitha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This service aims to introduce wayang culture and develop children's character education with the content of core competencies in spiritual attitudes, core competencies in social attitudes, core competencies in knowledge, and core competencies in skills by utilizing educational learning media. The subjects in this research were PAUD Mutiara Bunda and PAUD Kenanga, Pisang Candi, Sukun, Malang City. The results of this service show that the learning method through wayang literacy and local wisdom for early childhood has succeeded in becoming a means for teachers to introduce character-based local culture to early childhood